Advances in Mucosal Immunology 1990
DOI: 10.1007/978-94-009-1848-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T cell receptors TcR1 (gamma/delta) and TcR2 (alpha/beta) in the human intestinal mucosa

Abstract: Cryostat sections of normal human adult gastrointestinal mucosae were studied by double-label immunofluorescence with antibodies to CD3, CD4, CD8, CD5 and CD6, in parallel with antibodies fF1 and TCR61 against fl-chains and 6-chains of the T-cell receptor (TcR) types TcR2 (a/f) and TcRl (y/6), respectively. Virtually no TcRl + were found within the lamina propria. In the epithelial compartment, TcR1 + cells were infrequent: in the small bowel, -2% of T cells were TcR1 + . In the colonic epithelium, the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
(24 reference statements)
2
25
0
Order By: Relevance
“…The size of this subset in the different lymphoid compartments was small; in peripheral blood, according to previously published data (41,42), the percentage of CD3 ϩ CD8 ϩ CD5 Ϫ cells within the CD8-expressing population was 5.2 Ϯ 2.8 (range, 10.2-1.0); the size of this subset was significantly lower in lymph nodes (1.3 Ϯ 0.8; range, 2.5-0.5; p Ͻ 0.01, according to the Mann-Whitney test) and tonsils (3.5 Ϯ 3.0; range, 7.9 -1.0); in these latter, probably due to the small number of samples examined, the difference from PBMC was not significant ( p ϭ 0.43).…”
Section: Phenotypic Characterization Of Cd3mentioning
confidence: 66%
“…The size of this subset in the different lymphoid compartments was small; in peripheral blood, according to previously published data (41,42), the percentage of CD3 ϩ CD8 ϩ CD5 Ϫ cells within the CD8-expressing population was 5.2 Ϯ 2.8 (range, 10.2-1.0); the size of this subset was significantly lower in lymph nodes (1.3 Ϯ 0.8; range, 2.5-0.5; p Ͻ 0.01, according to the Mann-Whitney test) and tonsils (3.5 Ϯ 3.0; range, 7.9 -1.0); in these latter, probably due to the small number of samples examined, the difference from PBMC was not significant ( p ϭ 0.43).…”
Section: Phenotypic Characterization Of Cd3mentioning
confidence: 66%
“…The frequency of TCRγδ + IELs in human intestinal epithelium ranges from 2% to 40%, depending on the segment of bowel sampled (27)(28)(29)(30). Several reports have shown that the frequency of TCRγδ + IELs is increased in the small intestine of patients with CD compared with healthy individuals (8)(9)(10)(11).…”
Section: Resultsmentioning
confidence: 99%
“…although the role they play in the immune system is still unclear [1], Postulated functions include immunity to mycobacterial antigens and heal shock proteins, epithelial immune surveillance and immunorcgulation [1 3). The development of the -, <^ TCR repertoire is ordered, with expression of certain variable region combinations at dilTercnt times in ontogeny [1], V(')l • ceils constitute a major fraction of y6 T cells in several epithelial sites [1,[4][5][6][7][8], although the localization ofyt^ Tcell subsets to epithelial sites is less protiotmccd ihan fn mice fl], yS T cc\h expressing cevXd 'in receptors are over-represented in the rheumatoid synovium [I,y-I4] and in active multiple sclerosis lesions 11,15.16], It is therefore possible that yd T cells have a general role in autoimmune diseases [1], Graves' disease (GD) is eaused by autoantibodies stimulating the thyroid stimulating hormone receptor, although the initiating factors remain unknown. Heat shock proteins, known y6 T cell antigens, may play a role in the pathogenesis of GD [17.18], and -/tiTcells have been reported to be increased in the Correspondence: A, P, Weetman.…”
Section: Introductionmentioning
confidence: 99%